Non‐segmental vitiligo and psoriasis comorbidity – a case‐control study in Italian patients. (26th February 2013) - Arunachalam, M.; Dragoni, F.; Colucci, R.; Berti, S.; Crocetti, E.; Galeone, M.; Conti, R.; Moretti, S.
Abstract Background A recent systematic evaluation of vitiligo and psoriasis comorbidity has not yet been reported in a large series of patients with vitiligo. Objective To investigate the practical/clinical implications in subjects with both vitiligo and psoriasis compared to those with vitiligo alone. Methods This was a case‐control study on 463 vitiligo patients in our clinic from March 2008 to April 2011. Medical assessment was performed by dermatologists using the modified Vitiligo European Task Force form. Results In an univariate analysis, inflammation/pruritus [odds ratio (OR) 2.42, P = 0.03], use of drugs that can induce psoriasis (OR 2.74, P = 0.01), a family history (FH) of psoriasis (OR 2.87, P = 0.02), cardiovascular disease (OR 5.70, P = 0.001), hypertension (OR 4.7, P = 0.006) and type 2 diabetes mellitus (OR 3.87, P = 0.004), were significantly correlated with patients exhibiting vitiligo and psoriasis comorbidity. A trend was found in personal history of cardiovascular disease in patients with both diseases (OR 2.99, P = 0.07). FH of vitiligo was significantly associated with patients having only vitiligo (OR 0.35, P = 0.05). Multivariate analysis demonstrated that inflammation/pruritus in vitiligo macules (OR 2.56, P = 0.047) and a FH of cardiovascular disease (OR 4.07, P = 0.02) were the most significant predictors of patients having both psoriasis and vitiligo, while the presence of organ‐specific autoantibodies (OR 0.24, P = 0.007) was significantly associated with patients having only vitiligo. Conclusion The presence of vitiligo and even mild psoriasis is significantly correlated with a family history of cardiovascular disease, a factor that requires greater attention and follow‐up with respect to that necessary for vitiligo patients.